OPTIMIZATION OF SAMA', BASHOR, AND AF'IDAH IN LEARNING THE SUBJECTS OF MORAL CREED IN MADRASAH IBTIDA'IYAH QODRATULLAH - Karmiza, Ebing; Muchtar, Aflatun; Sukardi, Ismail (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Islamic education is vital in determining and producing quality for the next generations; so far, Muslims have adopted more Western educational concepts. However, if Muslims examine more deeply, many Islamic concepts in the Qur'an that teach educational methods are more relevant to Muslims. This study will examine the